The Adversities Faced By Female Adolescents On Antiretroviral Therapy In The Ethekwini District, South Africa: Antiretroviral Therapy - Farhana Mahomed (STIKes Mandala Waluya Kendari, 2023)
Background: Adolescent females face many emotional and psychological challenges. They must be accountable, responsible, and head families when both parents are absent. This further becomes a challenge when they are infected with HIV at birth and are cared for by a sick parent, relative or a caregiver. Issues like stigma and a lack of support arises, resulting in psychological distress. For these reasons most female adolescents living with HIV are unable to adhere to antiretroviral treatment. The aim of the study was to understand the adversities faced by female adolescents on antiretroviral therapy in the eThekwini district. Methods: Qualitative research method in the form of in‐depth interviews were used for data collection and analysis. This was a phenomenology study which explored various experiences of HIV-positive female adolescents on antiretroviral therapy in the eThekwini District, South Africa. In-depth individual interviews were conducted with 15 purposively selected participants. Data was analyzed guided by the phenomenology framework for data analysis. Results: Two themes emerged from the study: social impact of HIV and sources of support. It indicated variation on how living with HIV affected the lives of the female adolescents. Conclusion: Female adolescents' experiences vary regarding the social impact of HIV and sources of support. The varied experiences have an impact on adherence to treatment, which, in turn, affects the adolescents’ quality of life. Based on the findings, it is recommended the development of individualized support and relevant information to female adolescents on ART by healthcare professionals, family members, and teachers to promote adherence.